Effect of feeding complete ration vis-a-vis conventional ration with and without green fodder on nutrient utilization and lactation performance in crossbred cows - Lade, M H; Tiwari, D P; Kumar, Anil (The Indian Journal of Animal Sciences, 2007)
A feeding trial for 150 days was conducted in 24 lactating crossbred cows (40 to 125 days in milk) divided into 4 groups of 6 each in a 2 x 2 factorial experimental design and fed 4 dietary treatments to know the effect of complete ration with and without green fodder versus conventional ration with and without green fodder on milk yield, milk composition and nutrient utilization. The cows in 4 groups were fed concentrate mixture, wheat straw and mixed green fodder separately (conventional ration with green fodder, treatment 1), concentrate mixture and wheat straw separately (conventional ration without green fodder, treatment 2), uniformly blended concentrate mixture, wheat straw and mixed green fodder (complete ration with green fodder, treatment 3) and uniformly blended concentrate mixture and wheat straw (complete ration without green fodder, treatment 4), respectively. The rations were formulated so as to support for maintenance and 10 litre milk yield. The dry matter intake ranged from 2.74 to 3.12 kg/100 kg body weight and 121.34 to 138.47 g/kg W0.75 and the values differed significantly amongst different groups. The feeding systems had no effect on M intake, however, supplementation of green fodder significantly improved the dry matter intake in lactating crossbred cows. DCP and TDN intakes per unit body size did not differ among the different groups of cows. The digestibility of DM, OM, CP, EE, CF and NFE was improved due to supplementation of green fodder. The digestibility of DM, OM, and NFE also improved due to complete feed system. The daily average milk yield ranged from 8.43 to 9.38 kg, FCM yield ranged from 9.42 to 10.48 kg, fat yield ranged from 407.24 to 464.16 g and solids-not-fat yield ranged from 788.65 to 912.41 g in different experimental groups. Milk yield, 4% FCM yield, fat yield and SNF yield in cows fed with either conventional or complete rations with green fodder were significantly higher than in cows fed with conventional or complete rations without green fodder, however, there was no significant difference between conventional and complete feeding systems. The total solids, fat, protein, lactose, ash and soids-not-fat contents in milk did not differ significantly among different dietary treatment groups of cows and were not affected due to feeding systems as well as green fodder supplementation. The gross and net energetic efficiencies for milk production ranged from 17.92 to 25.93% and from 31.67 to 51.27%, respectively. The gross energetic efficiency and net energetic efficiency for milk production were not affected due to feeding systems, however, green fodder supplementation had significant improvement in gross and net energetic efficiencies for milk production. The average values for gross efficiency of nitrogen utilization ranged from 22.71 to 29.43% and net efficiency of nitrogen utilization ranged from 34.79 to 50.91% and the values were also not affected due to feeding systems but green fodder supplementation had significant improvement on utilization of dietary as well as digestible nitrogen for milk production. It was concluded that feeding systems had no effect on dry matter intake, milk yield and milk composition but supplementation of green fodder is inevitable in improving the milk production and also in saving costly concentrate mixture. Complete feed system is advantageous in-maintaining the persistency in milk yield and to prevent rumen metabolic disorders.